Cancer screening in Australia: future directions in melanoma, Lynch syndrome, and liver, lung and prostate cancers - Marianne F Weber; Henry M Marshall; Nicole Rankin; Stephen Duffy; Kwun M Fong; Kate Dunlop; Lauren Humphreys; Amelia K Smit; Anne E Cust; Natalie Taylor; Gillian Mitchell; Yoon-Jung Kang; et al. (Public Health Research & Practice, 2019)
While Australia now has well-established national screening programs for breast, bowel and cervical cancers, research continues into the feasibility of developing systematic screening programs for a number of other cancers. In this paper, experts in their fields provide perspectives on the current state of play and future directions for screening and surveillance for melanoma, Lynch syndrome, and liver, lung and prostate cancers in Australia. Although the evidence does not support population screening, there may be opportunities to prevent thousands of deaths through systematic approaches to the early detection of lung cancer and melanoma, testing for Lynch syndrome, and organised surveillance for hepatocellular carcinoma among individuals at high risk – guided by targeted research. The paper also looks at what impact new prostate specific antigen testing guidelines are having on screening for prostate cancer.